2012
DOI: 10.1002/lary.22494
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conventional continuous positive airway pressure to continuous positive airway pressure titration performed with sleep endoscopy

Abstract: Results with conventional CPAP titration and endoscopy-assisted CPAP titration showed no statistically significant difference. Endoscopy-assisted CPAP is a cheaper and less time consuming alternative to conventional CPAP and has similar results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 20 publications
1
44
1
Order By: Relevance
“…The reason is that collapse of the epiglottis is not usually seen when the patient is awake. Furthermore, laryngeal obstruction may be a reason for intolerance of CPAP and failure of OSA surgery [9]. The most common type of epiglottis pathology in our study group was closing door epiglottis, when the epiglottis collapsed on the posterior wall of the hypopharynx during inspiration (Figure 2).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The reason is that collapse of the epiglottis is not usually seen when the patient is awake. Furthermore, laryngeal obstruction may be a reason for intolerance of CPAP and failure of OSA surgery [9]. The most common type of epiglottis pathology in our study group was closing door epiglottis, when the epiglottis collapsed on the posterior wall of the hypopharynx during inspiration (Figure 2).…”
Section: Discussionmentioning
confidence: 95%
“…Civelek et al demonstrated that the majority of adult OSA patients unable to tolerate CPAP have multilevel obstruction [9], and 15% had primary epiglottic obstruction in the hypopharynx. Primary epiglottic obstruction may not be amenable to CPAP, as positive pressure may further push a retroflexed epiglottis into the endolarynx [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We, therefore, embarked on the study to evaluate the differential effect of nasal CPAP (nCPAP) pressure settings on upper airway collapsibility of OSA patients as assessed during drug‐induced sleep endoscopy (DISE). DISE has been successfully used for CPAP titration, with the results comparable to the conventional manual CPAP titration in the sleep laboratory . It also plays an increasingly important role in evaluation of upper airway characteristics of OSA patients to tailor individual surgical treatment .…”
Section: Introductionmentioning
confidence: 99%
“…Increase in the number of DISE examinations is to be expected, not only because of the growing OSA awareness but, perhaps in the near future, also to cut healthcare system costs by means of CPAP titration during DISE instead of during a costly overnight in-hospital polysomnography [53].…”
Section: Discussionmentioning
confidence: 99%